Physics for Scientists and Engineers with Modern - Serway, Raymond A. (Cengage Learning, Inc, 2008)
Foreword. Acknowledgments. Introduction. PART I: OVERVIEW-TWO DECADES OF RISK MANAGEMENT. 1990-1999. CHAPTER 1: A Framework for Understanding... Management (Andrew W. Lo) Reprinted from the Financial Analysts Journal (January/February 1999):13-26. CHAPTER 4: Reporting and Monitoring Risk Exposure (Robert W. Kopprasch, CFA) Reprinted from AIMR... Conference Proceedings: Risk Management (April 1996): 25-33. 2000-Present. CHAPTER 5: Risk Management: A Review (Sebastien Lleo, CFA) Modifi ed from The Research Foundation of CFA Institute